Microbiota modifications in prehabilitation – the next step towards comprehensive preparation for surgery. The scoping review - Łoniewski, Igor; Banasiewicz, Tomasz; Sieńko, Jerzy; Skonieczna-Zydecka, Karolina; Stachowska, Ewa (Gastroenterology Review/Przegląd Gastroenterologiczny, 2024)
This scoping review highlights the role of microbiota modifications in prehabilitation for surgical patients. It emphasises the importance of optimising gut microbiota through probiotics, synbiotics, and postbiotics to reduce surgical complications, such as surgical site infections (SSIs). The review highlights that gut dysbiosis, worsened by surgery, stress, antibiotics, and poor diet, can lead to increased infection risk and slower recovery. Evidence from systematic reviews, meta-analyses, and randomised controlled trials suggests that microbiota-targeted interventions can reduce SSIs, enhance immune responses, and promote quicker recovery. The review advocates for an individualised approach to prehabilitation, incorporating microbiota modifications based on patient-specific factors and surgery type. However, it also notes the need for further research to standardise therapeutic regimens and confirm the safety and efficacy of these interventions in clinical practice.